2021
DOI: 10.33805/2572-6978.153
|View full text |Cite
|
Sign up to set email alerts
|

Management of Mandibular Fractures: Report of Three Cases

Abstract: The mandibular bone is an important component of the facial bone, which has a unique role in digestive system, speech, and facial esthetics. For these important functions of mandibular bone, it is vital that surgeons should not only treat function but also consider the esthetics together. Mandibular fractures are among the most common traumatic injuries of the maxillofacial, and it is in facial region, the second most frequently fractured adult facial bone is the mandible due to its vulnerable position and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…21 The arch bar is kept in place for up to eight weeks because it accommodates for new bone formation between fracture fragments. 21,22 A subjective examination of the patient revealed that the mandibular fracture was caused by a fight that occurred one month prior to the patient's visit to the oral surgery clinic of Nala Husada Hospital. The patient's fracture fragment did not heal because she was not immediately treated for her injury and was only given painkillers (neglected fracture).…”
Section: Discusionmentioning
confidence: 99%
“…21 The arch bar is kept in place for up to eight weeks because it accommodates for new bone formation between fracture fragments. 21,22 A subjective examination of the patient revealed that the mandibular fracture was caused by a fight that occurred one month prior to the patient's visit to the oral surgery clinic of Nala Husada Hospital. The patient's fracture fragment did not heal because she was not immediately treated for her injury and was only given painkillers (neglected fracture).…”
Section: Discusionmentioning
confidence: 99%